Non-linear viscoelasticity and two-step yielding in magnetorheology: a colloidal gel approach to understand the effect of particle concentration - Segovia Gutiérrez, J. P. (2012)
The yielding behavior of conventional magnetorheological (MR) fluids is revisited for a wide range of magnetic fields and particle concentrations under a colloidal gel perspective. A two-step yielding behavior is found at intermediate magnetic fields (~10 kA/m) that can be explained as a transition from a strong-link to a weak-link (or transition) regime upon increasing the particle concentration in the MR fluid. This two-step yielding behavior is reminiscent of the classical concepts of static (frictional) and dynamic (Bingham) yield stress. By relating macroscopic elastic properties to a scaling fractal model, we could identify the prevalent gelation regime in MR fluids. VC 2012 The Society of Rheology